Optimizing the use of limited amounts of hydrogen in existing combined heat and power plants - J.F. Wiegner; N. Sürken; R. Neuhäuser; G. Gibescu; M. Gazzani (Renewable and Sustainable Energy Transition)
Combined cycle (CC) plants are expected to play an important role in balancing generation of heat and electricity from non-dispatchable renewable energy sources. In this work, we study different retrofit options for using hydrogen in CC plants to reduce the plant’s CO2 emissions. These options are: direct combustion in the gas turbine, supplementary firing in the heat recovery boiler (duct burner), and oxy-fuel combustion of hydrogen for direct steam production.Therefore, we first simulate the performance of an exemplary CC plant in a detailed non-linear process model. Second, we fit a surrogate, mixed-integer-linear model that can optimize the plant operation within a reasonable computation time over a long time frame (one year, with hourly resolution). This surrogate model allows for an in-depth analysis of hydrogen combustion retrofits in CC plants, assessing both profitability and environmental impacts. The findings suggest that direct combustion of hydrogen in the gas turbine becomes economically viable only when hydrogen is cheaper than natural gas. Although a duct burner fired by natural gas can enhance the plant’s profitability, it also increases the specific carbon emissions. Burning hydrogen in a duct burner, however, is not cost-effective. Retrofitting the steam cycle of the plant with an oxy-fuel hydrogen burner, however, can improve both profitability and CO2 emissions of electricity and steam generation.